DEFINITION AND BASIC ELEMENTS TYPES OF DECISIONS INDIVIDUAL FACTORS IN DECISION-MAKING GROUP DECISIONS TECHNIQUES FOR GROUP DECISION-MAKING - Iwan Irwandi; Rasad Mulyadi; Zakaria Syafei; Eka Sri Mulyani; Rijal Firdaos (Cakrawala Pedagogik, 2026)
This study aims to conduct an in-depth examination of the concept of decision-making in educational organizations, particularly from the perspective of Islamic educational management. The approach used is qualitative, specifically library research, through the analysis of various sources such as books and scholarly articles. The results of the study indicate that decision-making is a multidimensional process involving rational aspects, individual factors, and group dynamics. In addition to systematic stages such as problem identification, information gathering, and evaluation of alternatives, decisions are also influenced by perceptions, experiences, values, and individual cognitive abilities. In a group context, decision-making offers the advantage of diverse perspectives, although it faces challenges such as dominance and groupthink. In Islamic education management, the values of consultation, justice, and responsibility serve as the primary foundation. The integration of rational aspects and spiritual values contributes to more effective, participatory, and value-oriented decision-making.